New Scientific Progress Perspective with Proposed Revision of Current Physics Fundamentals - Neuville, Stephane (Archives of Case Reports, 2025)
Conversely to widespread popular belief, different elder and newly established theories, including quantum mechanics, the theory of relativity, and of quantum vacuum, are not satisfactory in giving an account for different experimentally observed physical effects. This is considering that the corresponding physical qualitative description of observed effects, has not to be confused with its Mathematical-Physics treatment, which provides some virtual hypothetical statements. To be mentioned in a first step, the solid-state material physics and the undetermined time/location of quantum states, concerning the interpretation of the Raman effect, of Superconductivity and Semiconducting properties and of some endothermal material phase transitions of better performing advanced carbon materials which can then be used for many more demanding solid-state optoelectronic and mechanical applications, including the determination of the carbon phase content of asteroid providing improved knowledge on their origin. With the next steps, we discuss the validity of the developed theories of relativity and of quantum vacuum energy, referring to identified anomalies concerning the fundamentals of the optical properties of light, the description of the particle/wave duality, and the interpretation of the Doppler effect, and about the deflection of a light beam by some celestial bodies. All these, coming out to the rejection of the theoretical mathematical concept of the Space/Time curvature, and to some rehabilitation of the absolute Aether with newly defined specific properties. Last one, suggested to give account for several observed physical effects to be better complete interpreted, and particularly concerning the entanglement of distant subatomic particles, the interference pattern of discontinuously emitted single particles through young slits and the propagation speed of the light and of gravity waves which is suggested to be not constant, and which are opening new perspectives for an improved knowledge of the Universe.